1 - (6x+3)-(x-4)(2x+1)=
3(2x+1)-(x-4)(2x+1) = (2x+1)(3-(x-4)) = (2x+1)(3-x+4) = (2x+1)(7-x)
2 - 4x² - 16 + (2x+3)(x-2) ⇒ 4x² - 16 est de la forme a²-b² = (a+b)(a-b)
= (2x-4)(2x+4) + (2x+3)(x-2) = 2(x-2)(2x+4) + (2x+3)(x-2) =
(x-2)(2(2x+4) + (2x+3)) = (x-2) (4x+8+2x+3) = (x-2)(6x+11)
3 - (x²-9)(2x+1) - (x-3)(2x+1)² = (x-3)(x+3)(2x+1) - (x-3)(2x+1)(2x+1) =
(x-3)(2x+1)(x+3-(2x+1) = (x-3)(2x+1)(x+3-2x-1) = (x-3)(2x+1)(2-x)
4 - 3(2x-1) + (x+2)(2-4x) = 3(2x-1) +(x+2)(2x-1)*-2 = (2x-1)(3 -2(x+2)) =
(2x-1)(3-2x-4) = (2x-1)(-2x-1)